An Overview of School Health Program Implementation among Elementary Schools in Banda Aceh - Asniar Asniar; Nailul Kharisma (Jurnal Ilmu Keperawatan, 2018)
The training and guidance for chaperones of school health program (Usaha Kesehatan Sekolah or UKS) are very essential to support the entire implementation of Trias UKS (three programs of UKS).  These programs are expected to prevent health problems on elementary school students such as stunting, underweight, obesity, anemia, worm disease, caries, diarrhea, hepatitis, asthma and cancer that will affect their growth and development. The purpose of this study was to explore the school health program implementation and its related factors among elementary schools in Banda Aceh. The design of study is descriptive explorative using cross sectional study approach. This study involved 30 UKS chaperones in elementary schools which were recruited by simple random sampling method. The data were collected by the questionnaire which was modified from School Health Index, and was completed by self-reported or guided-interview method. The results show that the School Health Service generally was at a good level of implementation (60%). In addition, the factors related to the implementation of UKS, namely perceived benefit (56,7%), perceived barriers (53,3%), perceived self-efficacy (53,3%), activity-related affect (50%), interpersonal influences (63,3%), and situational influences (50%), were identified at the good levels. This study recommends the District Health Office to conduct a continuous supervision on UKS, and empowered the chaperones of UKS and school communities to improve UKS implementation for the health of school-age children.Keywords: School Health Service, Chaperones, Elementary School